Features of Life Meaning Orientations and Defensive-Coping Behaviour of Russian and Foreign Students - E. L. Perchenko; T. V. Gudina (Высшее образование в России)
The relevance of the study is due to the need to comprehend the influence of cultural and value orientations on the behavior of Russian and foreign students in difficult situations. Relying on meaningful life guidelines helps to transform and improve one’s own line of response at difficult social crisis conditions and accumulate a baggage of culturally acceptable solutions. The need to understand this problem determined the purpose of the study – to identify features in the manifestation of meaningful life orientations and differences in the strategies of protective coping behavior among Russian and foreign students (from the Republic of Tajikistan). Based on the set goal, using empirical and interpretive research methods, results were obtained for a total sample of 100 people. The subjects were first-year students from Tajikistan and Russia. It was revealed that Russian students in crisis situations actively try to comprehend it and, nevertheless, satisfy their significant needs, while foreign young people, most often, smooth out, mitigate discomfort, their behavior is compensatory in nature. Nevertheless, differences in value-semantic orientations and, in accordance with this, building their own trajectory of protective and coping behavior allow students to adapt in society, coordinating their traditional values  with the modern cultural transformation of society.